Materiality, Experience and the Body: The Catholic Pilgrimage of Sheshan in Shanghai, China - Huang, Jianbo (Religions, 2023)
This paper foregrounds the Turnerian experiences of pilgrims themselves, for whom pilgrimage is perhaps first and foremost the process of experiencing faith with their whole body and mind. At the Chinese Catholic pilgrimage site of Sheshan, located in western Shanghai, multiple meanings and possibilities are written onto the body of the pilgrim as it interacts with sacred materialities. In the process, the pilgrim materially orients themselves towards the transcendent other and to people and events throughout time. The boundary between subject and object is increasingly blurred in the pilgrim’s imagination, and pilgrimage becomes a ‘porous’ mind-body experience for them. In the process, as pilgrims repeatedly physically enact doctrine and doctrinal texts in the course of pilgrimage—while simultaneously rooting them in their own personal lives—Sheshan is, through the concrete actions of worshippers layered up over time, continually being re-made as sacred.